1997 год. Осенняя сессия, 31 октября - 19 ноября - Теплова М. О. (2000)
Экземпляры: КХ (20010328) / Инвентарный номер: 1038915 / Цена: 20.00 / Сис.шифр: 67.400 / Авт.знак: Г 72 / ГРНТИ: 10 / ББК: 67.400.621